PENDEKATAN NARATIF: MEMAHAMI CHILDFREE SEBAGAI AKTUALISASI MAKNA HIDUP INDIVIDU MELALUI KISAH PENGALAMAN DI INSTAGRAM - Manggalaningwang, Jody; Rahardjo, Alexandra Rianti Grandi; Prasetya, Denny; Aritonang, Eva Reh Ulina; Simanjuntak, Magda Sabrina Theofany; Ullyana, Yuditha Franciska (KOMUNIKOLOGI: Jurnal Ilmiah Ilmu Komunikasi, 2024)
The decision to be childfree is a decision that is still considered to be anti-mainstream, so they are vulnerable to cynicism and public rejection. Individuals with identities that differ from generally accepted norms usually use social media as a medium for self-actualization. This study adopts a constructivist research paradigm and employs a narrative methodology involving in-depth interviews with six childfree participants. Thematic analysis was applied to the collected data. The study reveals that participants from diverse backgrounds share a common perspective on what constitutes a meaningful life, which differs from the prevailing societal norms in Indonesia. It highlights the importance of a well-defined self-concept in achieving psychological fulfillment among childfree individuals. Interestingly, social media serves primarily as a tool for sharing, networking, and dispelling misconceptions about the childfree lifestyle. Rather than seeking self-validation or actively promoting their choice, childfree individuals view social media to communicate the outcomes of their interactions with society. This study highlights the lives of individuals who choose to be childfree when using social media without hiding their identity as an effort to build respectful social relationships. Thus, childfree individuals interpret Instagram as only a medium for conveying the results of the interaction process with the environment, instead of self-validation.Keywords: childfree; Instagram; self-actualization